Being the next of kin of an older person living in a nursing home: an interview study about quality of life - Helena Rosén; Lina Behm; Birgitta Wallerstedt; Gerd Ahlström (BMC Geriatrics, 2019)
Abstract Background The length of stay in nursing homes before death in Sweden has significantly decreased, and nearly one-third of people die within 6 weeks of entering a nursing home. Support for the next of kin is one of the cornerstones of palliative care, but the principles are not always adhered to as recommended when caring for the elderly, which can affect the quality of life of their next of kin. The aim of this study was to explore the experiences of quality of life among the next of kin of older persons who live in nursing homes before an educational intervention of palliative care. Methods This is an explorative qualitative interview study with 40 next of kin using qualitative content analysis performed at baseline before the implementation of the principles of palliative care in nursing homes. Results The next of kin’s experiences of quality of life were expressed in three themes: Orientation to the new life situation, Challenges in their relationship and the Significance of the quality of care in the nursing home. The next of kin experienced a sense of relief, although the older person was constantly on their minds, and they could feel lonely. The difference in the couple’slife situations was experienced as burdensome by the next of kin. The challenges in the relationship were described as stressful, related to a guilty conscience and the older person’s vulnerability. The nursing home could be a context facilitating good relations. The perceptions of quality of care in terms of person-centredness affected the quality of life of the next of kin. Conclusions The findings show that four factors are decisive for the quality of life of next of kin: the relationships within the family, the degree of relief that nursing home care entails as compared to home care, the older person’s health status and whether the care is person-centred. Increased knowledge and education regarding palliative care in nursing homes are needed to better meet the needs of next of kin. Implementation of palliative care should take into account the need for support for next of kin. Trial registration NCT02708498, 15 March 2016.